Critical Action Inquiry for the Establishment of a Global Food Security Graduate Certificate in Latin America and the Caribbean at Texas Tech University - Carla Andrea Millares Forno; Todd Brashears; Amy E. Boren-Alpizar; Matt Baker; Carlos Carpio (Journal of International Agricultural and Extension Education, 2018)
The purpose of the study was to determine the topics and courses of a graduate certificate focusing on Global Food Security (GFS) for Latin America and the Caribbean (LAC) through critical action inquiry. GFS is a major issue worldwide that will continue to expand in years to come. Almost 795 million people are estimated to have suffered from chronic hunger globally in 2014-2016. Studies have shown the strong relationship between education and food security and we do not argue for causation, merely association. For this reason, curricula focused on teaching GFS to graduate students will enable professionals in international settings to manage the complexities of food security more effectively. For this critical action inquiry study, identification of the content was the result of a three-round Delphi study performed with experts from LAC and its comparison with the result of the Texas Tech University (TTU) professors survey to determine the topics and courses. Of the 91-originally-idenified topics, 40 reachedexperts’ consensus. The topics were then grouped into 23 courses. Faculty from TTU also ranked the courses. In the end, seven courses emerged from the research. The curriculum was approved and directed toward professionals in Latin America and the Caribbean. The courses for the online and face-to-face delivery of this multidisciplinary graduate certificate comprise the four pillars of food security and cross-cutting topics
Keywords: Delphi; food security; critical action research; curriculum; expert